Cerebello-cortical functional connectivity may regulate reactive balance control in older adults with mild cognitive impairment - Kannan, Lakshmi; Bhatt, Tanvi; Ajilore, Olusola (Frontiers in Neurology, 2023)
Background Older adults with mild cognitive impairment (OAwMCI) experience a two-fold increased risk of falling compared to their cognitively intact counterparts. This increased risk could be attributed to impairments in balance control mechanisms (both volitional and reactive), however, the exact neural substrates contributing to the balance impairments remain unclear. While changes in functional connectivity (FC) networks in volitional balance control tasks have been well highlighted, the relationship between these changes and reactive balance control has not been examined. Therefore, this study aims to explore the relationship between FC networks of the brain obtained during resting state fMRI (no visualization or active task performed) and behavioral measures on a reactive balance task in OAwMCI. Methods Eleven OAwMCI (< 25/30 on MoCA, > 55 years) underwent fMRI and were exposed to slip-like perturbations on the Activestep treadmill. Postural stability, i.e., dynamic center of mass motion state (i.e., its position and velocity) was computed to determine reactive balance control performance. The relationship between reactive stability and FC networks was explored using the CONN software. Results OAwMCI with greater FC in default mode network-cerebellum (r2 = 0.43, p < 0.05), and sensorimotor-cerebellum (r2 = 0.41, p < 0.05) network exhibited lower reactive stability. Further, people with lower FC in middle frontal gyrus-cerebellum (r2 = 0.37, p < 0.05), frontoparietal-cerebellum (r2 = 0.79, p < 0.05) and cerebellar network-brainstem (r2 = 0.49, p < 0.05) exhibited lower reactive stability. Conclusion Older adults with mild cognitive impairment demonstrate significant associations between reactive balance control and cortico-subcortical regions involved in cognitive-motor control. Results indicate that the cerebellum and its communications with higher cortical centers could be potential substrates contributing to impaired reactive responses in OAwMCI.